2019
DOI: 10.1029/2019gl084400
|View full text |Cite
|
Sign up to set email alerts
|

Drainage and Sedimentary Responses to Dynamic Topography

Abstract: Dynamic topography due to mantle flow contributes to shaping Earth's evolving landscapes by affecting sediment routing, which has rarely been explored in source-to-sink contexts. Here we design a generic model to investigate the impact of dynamic topography on both landscape evolution and stratigraphic formations. An imposed wave of dynamic topography propagates laterally under a fixed continent, exerting transient surface uplift and subsidence. We find that a migrating dynamic topography can induce significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…We show the importance of taking climate, dynamic topography as well as erodibility together as forcing parameters and not only focusing on one main driver as they appear to be completely interdependent. We agree that mantle dynamics can cause rapid uplift associated with drainage reorganisation, and denudation over a short period of time (Ding et al, 2019). Braun et al 2013, also showed that low slopes associated with the motion of a continent over a fixed source of dynamic topography may lead to substantial, i.e., kilometre scale, and rapid surface erosion, through continental-scale drainage reorganization.…”
Section: Discussionsupporting
confidence: 74%
“…We show the importance of taking climate, dynamic topography as well as erodibility together as forcing parameters and not only focusing on one main driver as they appear to be completely interdependent. We agree that mantle dynamics can cause rapid uplift associated with drainage reorganisation, and denudation over a short period of time (Ding et al, 2019). Braun et al 2013, also showed that low slopes associated with the motion of a continent over a fixed source of dynamic topography may lead to substantial, i.e., kilometre scale, and rapid surface erosion, through continental-scale drainage reorganization.…”
Section: Discussionsupporting
confidence: 74%
“…Dynamic topography undoubtedly makes a profound contribution to relative sea-level changes, ancient oceanic circulation, fluvial drainage patterns, and sedimentary deposition 62 67 . Here, we have shown that intraplate magmatism, positive asthenospheric temperature anomalies and thinned lithosphere are closely related during Neogene-Quaternary times.…”
Section: Discussionmentioning
confidence: 99%
“…Block landscape models showed that continent-scale tilting during early Late Cretaceous uplift was necessary to reproduce the major pulse of sediment to the marine basins on the west coast at that time (Braun et al, 2014). Additional modeling of a generic continent subjected to a propagating wave of dynamic topography argued that the modeled sedimentary architecture was consistent with Cretaceous sedimentary archives from southern Africa (Ding et al, 2019). Modeling efforts focused on river profile shape have taken this approach a step further by comparing modeled and observed river profiles to invert for uplift histories that suggest that the high topography was developed in the last 30-40 Ma (Paul et al, 2014;Roberts & White, 2010;Rudge et al, 2015).…”
Section: Tablementioning
confidence: 85%